Comunicação no processo de inovação tecnológica: relações entre ICT e o setor empresarial através dos NITs - Liberato, Tatiane Furukawa (Universidade Federal de São Carlos, 2018)
In recent years, the Scientific and Technological Institutions (STIs) have been increasingly betting on innovation, becoming more aware of the importance of the protection of the technologies developed in their research labs, as well as the need to transfer these results to society. In this context, the scientific dissemination of Technology Transfer Offices (TTOs) of these institutions can contribute to social development and to the innovative advancement of industry, as they are relevant sources of production and exchange of scientific knowledge. Given that the objective of the Offices is to encourage innovation through the training and use of the intellectual property system, and technology transfer, spreading this culture in the institution, the society and the state, this research aimed to analyze the scientific dissemination of large public Brazilian universities’TTOs, checking and managing of the communication is carried out, especially in the dissemination of intellectual property, which includes the business sector as a potential developer of technology generated in academia and therefore target audience of this process. Whereas science communication is a clarification instrument of society in relation to social impacts of science and technology, the work is based on the perspective of STS studies – Science, Technology and Society – as a promising field of research that seeks to identify the role of information to strengthen citizenship and participation in public policy research and development (R&D). The work considers the importance of the dissemination of scientific production, the interest of society in scientific affairs and the dissemination and democratization of knowledge considering the computerization of society, and the challenges and obstacles of this type of communication, in order to meet the new demands in the field of Intellectual Property and Technology Transfer. The results may provide an overview of dissemination of TTO’s, discussing weaknesses and trends and assisting in developing strategies and innovative communication practices for Brazilian STIs.
Communication in the process of technological innovation: relations between Scientific and Technological Institutions (STIs) and the business sector through Technology Transfer Offices (TTOs)
Keywords: Divulgação científica; Inovação tecnológica; Propriedade intelectual; Transferência de tecnologia; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; CIENCIAS SOCIAIS APLICADAS